Rainbows, roots, and magic shoots: oxford literacy web - Graham, Elspeth; Peet, Mal (Oxford University Press China, 2002)
Features extracts that cover the full range of text requirements for Year 2, as described in the National Literacy Strategy: fiction, non-fiction, poetry, stories by significant children's writers, traditional stories, recounts, institutional texts, and more. The texts are also linked by theme to enable a comparison across the ranges.